2018
DOI: 10.20532/cit.2018.1004123
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Efficient Recognition and Classification of Acute Lymphoblastic Leukemia with a Novel Customized-KNN Classifier

Abstract: Even in this modern era today, life's extent is still being challenged by many pathological diseases such as cancer. One such hazard is leukemia. Even a trivial setback in detecting leukemia lead to a severe outcome: the affected cells may eventually prove to be fatal. To combat this, we propose an algorithm to better segment the nucleus region of White Blood Cells (WBC) found in stained blood smear images with the intent of identifying Acute Lymphoblastic Leukemia (ALL). In our proposal, the image is made rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Furthermore, experimental outcomes revealed that the proposed model is more effective than previous works carried out for the classification of ALL. Umamaheswari and Geetha [17] GLCM+Statistical+Geometrical Features C-KNN 96.25 Tuba and Tuba [18] Shape+Texture features GAO-based methods 93.84 Singhal and Singh [15] LBP GLCM -------93.84 87.30 Praveena and Singh [16] GreyJOA…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, experimental outcomes revealed that the proposed model is more effective than previous works carried out for the classification of ALL. Umamaheswari and Geetha [17] GLCM+Statistical+Geometrical Features C-KNN 96.25 Tuba and Tuba [18] Shape+Texture features GAO-based methods 93.84 Singhal and Singh [15] LBP GLCM -------93.84 87.30 Praveena and Singh [16] GreyJOA…”
Section: Discussionmentioning
confidence: 99%
“…The study Umamaheswari and Geetha [17] developed a scheme for optimized identification and detection of ALL using a novel customized-KNN classification model. During the preprocessing stage of this work, the medical image was prepared for segmentation through changing its size, brightness, and contrast.…”
Section: Literature Surveymentioning
confidence: 99%
“…However, the scheme used is SVM, which attained 89.81% accuracy. In [47], the ALL-IDB2 dataset is used for the identification of ALL where the method investigated is customized KNN with 96.25% accuracy. In [48], by utilizing ALL-IDB1 dataset, ALL is classified on the basis of cell energy features by employing SVM, which attained 94.00% accuracy.…”
Section: Literature Surveymentioning
confidence: 99%
“…The features are thresholded to filter the leukocytes from some other background blood elements. After sampling a random set of images, the threshold of solidity, area, and perimeter are set as 0.80, 800, and 0.40 respectively (16) . It is done as:…”
Section: Feature Thresholdingmentioning
confidence: 99%